Investigation of different heaviside function forms in discontinuity problems - Nguyễn Mai Chí Trung; Nguyễn Ngọc Thắng (My University, 2025)
Investigation of different heaviside function forms in discontinuity problems
Keywords: Heaviside function; Discontinuity problems; Math modeling